Sense of coherence, off-job crafting, and mental well-being: A path of positive health development. (28th November 2022) - Tušl, Martin; de Bloom, Jessica; Bauer, Georg F
Summary: Our study examines the core concept of salutogenesis—sense of coherence (SOC)—in relation to off-job crafting (OJC) and mental well-being (MWB). The original salutogenic model of health mainly addresses the protective function of SOC against adversity. In our study, we focus on the recently proposed path of positive health development that captures how SOC can contribute to positive health and thriving. We present and test our theoretical assumptions about one such path, examining OJC as a possible mechanism how SOC translates into MWB. We tested our proposed model using cross-lagged panel model with three waves of panel data from Swiss and German employees ( N = 2217). We compared our model to alternative nested models and conducted indirect effect analysis to test longitudinal mediation. Our hypothesized model fitted the data well and we found support for our main hypothesis that OJC partially mediates the relationship between SOC and MWB. Further, we identified positive reciprocal relationships between SOC and MWB, as well as between OJC and MWB. Overall, our study provides evidence that OJC is one mechanism underlying the recently postulated path of positive health development in the salutogenic model. For health promotion, this implies that promoting SOC and OJC may help to strengthen individual well-being and lead to positive feedback loops that foster personal development and thriving.